Examination of the Relationship Between Social StudiesTeacher Candidates of Pre-Service Teacher IdentityLevels And Possible Self-Esteem Levels - (:unkn) unknown (My University, 2019)
This research was prepared to investigate the relationship betweenpossible self-esteem levels and prevocational teacher identity levels of socialstudies teacher candidates. The research was prepared in accordance with therelational screening model. In this research was used appropriate samplingmethod and the study, in the academic year of 2017-2018; Uşak University, MuğlaSıtkı Koçman University, Afyon Kocatepe University and Aksaray University havebeen conducted with 290 prospective teachers who have been educated in thedepartment of social studies teaching of the education faculties. The relationshipbetween prevocational teacher identity levels and probable self-esteem levels ofsocial studies teacher candidates has been investigated using the PearsonMoments Multiplication Correlation Analysis. As a result of the research, it wasseen that prevocational teacher identities and expected possible self-esteems ofsocial studies teacher candidates are high, and feared probable self-esteem arelow. It has been determined that social studies teacher candidates have a positivedirection, linear and intermediate relationship between their prevocationalteacher identity levels and their expected possible self-esteem levels. It has beendetermined that the social studies teacher candidates have a negative direction,linear and intermediate relationship between their prevocational teacher identitylevels and their feared possible self- esteem levels.